14th International Conference on Computer and Information Technology (ICCIT 2011) 2011
DOI: 10.1109/iccitechn.2011.6164779
|View full text |Cite
|
Sign up to set email alerts
|

Active queue management with adaptive codec bit rate variation in WLAN for efficient VoIP performance

Abstract: VoIP over Wireless LANs is greatly aff ected by path loss, RF interference and other sources of signal attenuation in addition to network congestion. The primary factors involved in effective real-time communication, namely delay and loss, must be within certain controlled limits in such a scenario. Wireless LAN Access Points must, therefore, act in tune with the codecs to ensure high quality of the ongoing VoIP sessions. In this paper, we analyze the various codec parameters with respect to wireless LAN APs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…Moller et al have shown in [16] that switching from one codec to another can improve the speech quality, if the former codec was suffering a high packet loss rate and if the latter codec significantly reduces the packet loss impact on the speech quality. Furthermore, in [17], the authors note that decreasing the transmission rate by increasing packet size is not an effective method of ensuring voice quality, possibly due to the fact that more voice data is lost when a packet is lost. To combat this, the authors proposed a similar switching method to [16].…”
Section: Related Workmentioning
confidence: 99%
“…Moller et al have shown in [16] that switching from one codec to another can improve the speech quality, if the former codec was suffering a high packet loss rate and if the latter codec significantly reduces the packet loss impact on the speech quality. Furthermore, in [17], the authors note that decreasing the transmission rate by increasing packet size is not an effective method of ensuring voice quality, possibly due to the fact that more voice data is lost when a packet is lost. To combat this, the authors proposed a similar switching method to [16].…”
Section: Related Workmentioning
confidence: 99%